2011
DOI: 10.1007/s00468-011-0651-x
|View full text |Cite
|
Sign up to set email alerts
|

Aridity promotes differences in proline and phytohormone levels in Pinus pinaster populations from contrasting environments

Abstract: We analysed proline, abscisic acid, (ABA), jasmonic acid (JA), indole acetic acid (IAA) and salicylic acid (SA) accumulation after summer drought at two Pinus pinaster provenance-progeny trial sites. The aim of the study was to evaluate P. pinaster phenotypic plasticity and intraspecific variation in the endogenous concentrations of these metabolites and to determine the best stress indicators for family and population discrimination. The environmental effect was remarkable, as striking differences between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
3
22
0
1
Order By: Relevance
“…de AIA endógeno em brotações juvenis e sua influência sobre a resistência a estresses ambientais, ampliando os índices de enraizamento de propágulos em espécies arbóreas (CORCUERA et al, 2012). Apesar da baixa emissão de brotações epicórmicas em árvores com 80 anos, estas apresentaram 47,5% de enraizamento, 10,3 raízes por estaca e 1,6 cm de comprimento de raízes para as técnicas de decepa no verão.…”
Section: Resultsunclassified
“…de AIA endógeno em brotações juvenis e sua influência sobre a resistência a estresses ambientais, ampliando os índices de enraizamento de propágulos em espécies arbóreas (CORCUERA et al, 2012). Apesar da baixa emissão de brotações epicórmicas em árvores com 80 anos, estas apresentaram 47,5% de enraizamento, 10,3 raízes por estaca e 1,6 cm de comprimento de raízes para as técnicas de decepa no verão.…”
Section: Resultsunclassified
“…Proline too is a well documented osmolyte involved in abiotic stress tolerance including heavy metal stress (Chandra et al, 2012;Corcuera et al, 2012;Diaz et al, 2014;Pandey & Gupta, 2015). Elevated levels of proline during stress conditions could be a result of increased catabolism of the phenolic compounds (Hamid et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring plant fitness and other functional features that allow adaptation and survival of plants in high‐mountain environments has contributed to proposing a number of potential physiological stress indicators. These can be very useful and valuable for different questions, such as evaluating the effects of extreme temperatures, drought and irradiance or anthropogenic disturbance on plant fitness (Corcuera et al , Wen and Chen ).…”
Section: Stress Indicators: Evaluating Adaptation Responses To Abiotimentioning
confidence: 99%
“…Carbon isotope (δ 13 C) and Pro content have been proposed as drought and temperature stress indicators in different plant species, given their link to water‐use efficiency and osmotic adjustment, respectively (Farquhar et al , Corcuera et al , Hayat et al ). In alpine species, studies in juniper needles reported a significant negative correlation among δ 13 C and Pro accumulation with soil water content and rainfall (Wen and Chen ).…”
Section: Stress Indicators: Evaluating Adaptation Responses To Abiotimentioning
confidence: 99%